The Daisy Chain Flower Shop - Gilmore, Laurie (Gilmore, Laurie. Dream Harbor series, 2026)
Daisy is fed up with being unlucky in love. And since Mayor Kelly declared her beloved flower shop cursed in one of his infamous visions, business has been slow. Dream Harbor newcomer Elliot has been adjusting to small-town life following his own relationship turmoil. And until now he's avoided the flower shop at all costs. If the mayor is correct, he doesn't need any more bad luck in his life. When he finds himself walking through the door of the Daisy Chain Flower Shop, he doesn't expect it to be a life-changing moment. But as the petals blossom in the sunlight, might the unluckiest woman in Dream Harbor finally find that love comes when you're least expecting it?